PENGARUH MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DI BADAN PENANAMAN MODAL DAN PELAYANAN PERIZINAN TERPADU KABUPATEN JEPARA - Widyanti, Chita; Sulandari, Susi; Lituhayu, Dyah (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Organization need resources to achieve their purpose. Human resources is one of important component in organization. How the human resources work will determine how the organization can achieve their purpose and how the organization's activities are carried out. The problem in this research is how the influence of motivation and organizational culture on employee performance in Badan Penanaman Modal dan Pelayanan Perizinan Terpadu Kabupaten Jepara. The purpose of this study is to determine how much influence the motivation and organizational culture on employee performance.This research is a quantitative research and the respondents are employees of Badan Penanaman Modal dan Pelayanan Perizinan Terpadu Kabupaten Jepara. Data collection methods use questionnaires. Data analysis techniques that used to answer the research objectives is Kendall Tau.Based on this research, it is known that employee performance and organizational culture in category â€œbaikâ€. While the motivation in the category â€œcukup baikâ€. Correlation test showed that motivation does not have a relationship and does not affect employee performance, organizational culture has a relationship and affect employee performance, while simultaneously motivation and organizational culture have a positive and significant relationship and effect on employee performance.